2012
DOI: 10.2478/s13380-012-0046-5
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive deficits, obesity and disability in schizophrenia

Abstract: Despite 50 years of pharmacological and psychosocial interventions schizophrenia remains one of the leading causes of disability. The inability to function in everyday settings includes deficits in performance of social, occupational, and independent living activities. Schizophrenia is also a life-shortening illness, caused mainly by poor physical health and its complications. Dysfunctional lifestyles including sedentary behavior and lack of physical activity prevail, while treatment with adipogenic antipsycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 89 publications
(65 reference statements)
2
23
0
Order By: Relevance
“…Domains of physical performance, neuromuscular and psychomotor deficits are all eminently modifiable in the general population, and as we have shown, in schizophrenia Strassnig et al, 2012. We believe that an accurately defined ‘holistic approach’ to disability reduction in schizophrenia, accounting for these domains, offers tremendous opportunity to move the disability burden in a positive direction.…”
Section: Implications For Schizophreniamentioning
confidence: 72%
“…Domains of physical performance, neuromuscular and psychomotor deficits are all eminently modifiable in the general population, and as we have shown, in schizophrenia Strassnig et al, 2012. We believe that an accurately defined ‘holistic approach’ to disability reduction in schizophrenia, accounting for these domains, offers tremendous opportunity to move the disability burden in a positive direction.…”
Section: Implications For Schizophreniamentioning
confidence: 72%
“…Regular physical exercise induces neurobiological, functional and structural brain changes associated with cognition (and by inference, functional capacity) and psychiatric symptoms in severe mental illness (Strassnig et al, 2012b). For example, one study in schizophrenia showed improvement in memory after only a short exercise period of 12 weeks, commensurate with relative increases in hippocampal volume of 12% and no change in a non-exercise group of patients (-1%) (Pajonk et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…Rather, they likely suggest that cognitive impairments may contribute to the development of physical limitations. Obesity in schizophrenia is correlated with multiple impairments in nonsocial and social cognition. On the nonsocial side, decision‐making regarding dietary choices has been shown to be impaired.…”
mentioning
confidence: 99%